2021
DOI: 10.3389/fevo.2021.702848
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Variation of Asymbiotic Nitrogen-Fixing Microorganisms in Alpine Grasslands on the Tibetan Plateau

Abstract: Asymbiotic nitrogen-fixing (ANF) bacteria contribute a substantial amount of nitrogen in ecosystems, especially in those with low symbiotic nitrogen fixation (SNF) capability. Degradation of alpine grassland is widespread on the Tibetan Plateau and sown grassland has become one of the main strategies for grassland restoration. However, the diversity and community structure of ANF bacteria in different grassland types remain unknown. The aim of this study was to fill this gap. Soil samples were obtained from 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Nitrogen is prominently present in the atmosphere in a gaseous form which is impassable to plants and animals. Assimilation of nitrogen by plants, atmospheric nitrogen is required to convert into ammonia, and this conversion is driven by nitrogenase enzymatic complex containing nitrogen-fixing microorganisms and the process called biological nitrogen fixation ( Li et al, 2021 ). Rhizobia is the universal group of bacteria to fix nitrogen which is abundantly present in the rhizospheric area of soil ( Shimonda et al, 2020 ).…”
Section: Pgpr Mechanisms and Their Beneficial Activitiesmentioning
confidence: 99%
“…Nitrogen is prominently present in the atmosphere in a gaseous form which is impassable to plants and animals. Assimilation of nitrogen by plants, atmospheric nitrogen is required to convert into ammonia, and this conversion is driven by nitrogenase enzymatic complex containing nitrogen-fixing microorganisms and the process called biological nitrogen fixation ( Li et al, 2021 ). Rhizobia is the universal group of bacteria to fix nitrogen which is abundantly present in the rhizospheric area of soil ( Shimonda et al, 2020 ).…”
Section: Pgpr Mechanisms and Their Beneficial Activitiesmentioning
confidence: 99%
“…For example, pioneer plants ( Serianthes calycina and Gymnostoma webbianum ) regulated bacterial functional groups involved in the N-cycle in the Nickel mine soils ( Héry et al, 2005 ). Moreover, the effects of forage culture on microbial functional groups may drive the progress of grassland ecological restoration ( Fry et al, 2017 ; Li et al, 2021 ). A study showed that planting gramineous forage ( Elymus nutans ) increased the diversity and activity of asymbiotic nitrogen-fixing bacteria, which may promote soil function recovery and degraded grassland restoration ( Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effects of forage culture on microbial functional groups may drive the progress of grassland ecological restoration ( Fry et al, 2017 ; Li et al, 2021 ). A study showed that planting gramineous forage ( Elymus nutans ) increased the diversity and activity of asymbiotic nitrogen-fixing bacteria, which may promote soil function recovery and degraded grassland restoration ( Li et al, 2021 ). However, forage culture rapidly increases plant biomass, which may cause an increase in plant pathogen abundance, thus inhibiting plant growth and grassland restoration rates ( Kardol and Wardle, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation